2018
DOI: 10.1186/s12889-018-5678-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of indoor air purification in treating Artemisia (mugwort) pollen allergic rhinitis: study protocol for a randomised controlled trial

Abstract: BackgroundAllergic rhinitis (AR) is a worldwide health problem. Allergen avoidance is strongly recommended for AR patients. Air purification can reduce concentrations of particles in indoor air, including those of allergens. Air purifiers have been recommended by clinicians for AR patients, but few studies have focused on the removal of airborne allergens from home environments. Such studies have been limited by a lack of blinding, small samples, or a failure to measure allergen levels, disease activity, or a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
4
1
1
Order By: Relevance
“…The most common aeroallergen detected in our study was artemisia (14.47%), which is not consistent with the highest dust mite reported in other Chinese regions [5][6][7][8][9]. Moreover, the positive rate of artemisia was mounting up from spring to autumn and reached its maximum (29.09%) in August, which is the growing season of Artemisia.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The most common aeroallergen detected in our study was artemisia (14.47%), which is not consistent with the highest dust mite reported in other Chinese regions [5][6][7][8][9]. Moreover, the positive rate of artemisia was mounting up from spring to autumn and reached its maximum (29.09%) in August, which is the growing season of Artemisia.…”
Section: Discussioncontrasting
confidence: 91%
“…These results suggest that children in the region should wear masks to avoid exposure to these seasonal allergens. Some studies also showed indoor air purifiers used could improve nasal congestion, sneezing, runny nose, itchy eyes, tearing, and other allergy symptoms [8]. The following aeroallergen was cat dander.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol and details of the physiological and biochemical assessments undertaken have been described previously . This study was implemented in Yulin City from June 2016 to September 2018.…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol and details of the physiological and biochemical assessments undertaken have been described previously. 13 This study was implemented in Yulin City from June 2016 to September 2018. We enrolled patients with AR, based on the definition outlined by ARIA, 14 and those who showed sensitivity to the allergens of Artemisia pollen in the recruitment radioallergosorbent test (RAST).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Nuolatinis AR trunka daugiau nei 4 dienas per savaitę arba ilgiau nei 4 savaites. Sergant NAR, svarbu nustatyti konkrečius alergenus, kuriems įsijautrinama ir tinkamai prižiūrėti patalpų orą [24]. Nuolatinio AR klinika ne visada gali būti tokia ryški, kaip sergant sezoniniu AR, todėl medikamentinis gydymas gali skirtis.…”
Section: Tyrimo Rezultataiunclassified